Grazing Adaptability of Beef Cattle on the Dwarf Napiergrass (Pennisetum purpureum Schumach) Pasture - A. Ako (Media Peternakan, 2007)
Grazing adaptability of beef cattle on dwarf variety of late-heading type (DL) napiergrass (Pennisetum purpureum Schumach) pasture was examined in summer season at Miyazaki, Japan in 2005. Five paddocks of DL napiergrass pasture with an area 2500 m2, (500 m2, per paddock) were established since May 2002. Three heads of raising beef cows (Japanese-Black) were rotationally grazed in a week with 4-weeks rest period from June to October. Forage dry yield at pre- and post-grazing averaged 238.6 – 582.6 g/m2 and 152.8 – 309.5 g/m2, respectively with percentage consumption averaged 42.5% – 71.6%. Forage consumption and dry matter intake averaged 14.5 – 50.9 g DM/m2/day and 2.42 – 8.48 kg DM/1 IU/day, respectively with average daily gain was 0,56 kg/day. Grazing adaptability of beef cattle on DL napiergrass needed time for about one week. Thus, the DL napiergrass pasture can be utilized under the rotational grazing at stocking rate of 12 head/ha (calculated 3600 kg LW/ha/day) in the summer season of subtropical area.